An Investigation of Tenascin-C Levels in Rheumatic Mitral Stenosis and Their Response to Percutaneous Mitral Balloon Valvuloplasty - Celik, Ahmet; Gunebakmaz, Ozgur; Baran, Oguzhan; Dogdu, Orhan; Elcik, Deniz; Kobat, Mehmet Ali; Topsakal, Ramazan (Karger, 2013)
Objective: The purpose of this study was to evaluate the tenascin-C levels in severe rheumatic mitral stenosis before and after percutaneous mitral balloon valvuloplasty (PMBV). Subjects and Methods: Forty patients with severe mitral stenosis requiring PMBV and 20 age-matched healthy subjects were included in the study. The mitral valve areas, mitral gradients and systolic pulmonary artery pressure (sPAP) were measured by echocardiography. The sPAP values and mitral gradients were also measured by catheterization before and after PMBV. The blood tenascin-C levels were measured before PMBV and 1 month after the procedure. Results: The echocardiographic mean mitral gradients had a significant decrease after PMBV (11.7 +/- 2.8 vs. 5.6 +/- 1.7 mm Hg; p < 0.001) and also those of catheterization (13.9 +/- 4.4 vs. 4.0 +/- 2.4 mm Hg; p < 0.001). Mitral valve areas increased significantly after PMBV (from 1.1 +/- 0.1 to 1.8 +/- 0.2 cm(2), p < 0.001). Tenascin-C levels decreased significantly in patients after PMBV (from 15.0 +/- 3.8 to 10.9 +/- 3.1 ng/ml; p < 0.001). Tenascin-C levels were higher in patients with mitral stenosis before PMBV than in healthy subjects (15.0 +/- 3.8 and 9.4 +/- 2.9 ng/ml; p < 0.001, respectively). There were no significant differences between patients with mitral stenosis after PMBV and healthy subjects (10.9 +/- 3.1 and 9.4 +/- 2.9 ng/ml; p = 0.09, respectively). There was a significant positive correlation between tenascin-C levels and sPAP (r = 0.508, p < 0.001). In multivariant analysis, tenascin-C predicted mitral stenosis (p = 0.004, OR: 2.31). Conclusions: Tenascin-C was an independent predictor for rheumatic mitral stenosis. Copyright (C) 2012 S. Karger AG, Basel
Keywords: Tenascin-C; Mitral stenosis; Percutaneous mitral balloon valvuloplasty; Pulmonary hypertension